2003
DOI: 10.1097/01.wcb.0000071887.63724.b2
|View full text |Cite
|
Sign up to set email alerts
|

BOLD and Perfusion Response to Finger-Thumb Apposition after Acetazolamide Administration: Differential Relationship to Global Perfusion

Abstract: Summary:The authors studied the effects of altering global cerebral blood flow on both blood oxygen level-dependent (BOLD) response and perfusion response to finger-thumb apposition. A PICORE/QUIPSS II protocol was used to collect interleaved BOLD-weighted and perfusion-weighted images on eight finger-thumb apposition trials. Subjects were studied on a drug-free day and on a day when acetazolamide was administered between the second and third trials. After acetazolamide administration, resting cortical perfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 40 publications
11
98
0
1
Order By: Relevance
“…Interestingly, however, the CBF change (DCBF) appears to remain the same despite the baseline change (Ances et al, 2001;Kastrup et al, 2002;Li et al, 1999Li et al, , 2000. Similar results have been found with injection of acetazolamide, a carbonic anhydrase inhibitor (Brown et al, 2003). Carbonic anhydrase catalyzes the conversion of CO 2 to bicarbonate ions, which increases the carrying capacity of the blood for removing CO 2 .…”
Section: Experimental Characterization Of the Hemodynamic Responsesupporting
confidence: 66%
See 1 more Smart Citation
“…Interestingly, however, the CBF change (DCBF) appears to remain the same despite the baseline change (Ances et al, 2001;Kastrup et al, 2002;Li et al, 1999Li et al, , 2000. Similar results have been found with injection of acetazolamide, a carbonic anhydrase inhibitor (Brown et al, 2003). Carbonic anhydrase catalyzes the conversion of CO 2 to bicarbonate ions, which increases the carrying capacity of the blood for removing CO 2 .…”
Section: Experimental Characterization Of the Hemodynamic Responsesupporting
confidence: 66%
“…Experiments have found that when baseline CBF is increased by breathing CO 2 or administering acetazolamide, the BOLD response is reduced. For example, Brown et al (2003) found that acetazolamide raised baseline CBF by 20% and the BOLD response in the motor cortex with finger tapping was reduced by 35%, but the CBF change (DCBF) with activation stayed the same.…”
Section: Effect Of the Physiological Baseline On The Bold Responsementioning
confidence: 99%
“…Although increases in blood flow velocity and cerebrovascular resistance dissipate from 3 to 28 days of abstinence in adults with marijuana use levels consistent with this sample (i.e., 15.9 days per month), very heavy users remained abnormally elevated (Herning et al 2005). Thus, increased BOLD response in adolescent marijuana users could reflect residual cerebrovasculature abnormalities, although increased blood flow or volume would likely yield lower BOLD response (Brown et al 2003), not greater, as seen here.…”
Section: Discussionmentioning
confidence: 65%
“…BOLD reproducibility is influenced by changes in the baseline state caused by differences in physiologic or pharmacologic states (Brown et al 2003;Cohen et al 2002), or simply by differences in attention during different runs. The majority of BOLD reproducibility studies either examined: 1) the spatial reproducibility of the volume of activation (Rombouts et al 1998;Tegeler et al 1999) or 2) the stability of the dynamics of the hemodynamic response function (HRF) in the context of an event-related study (Aguirre et al 1998;Handwerker et al 2004).…”
Section: Discussionmentioning
confidence: 99%